Implementation of Data Logging and Historical Graphs of Furnace Temperature at the Electrical Engineering Department Laboratory, Manado State Polytechnic - Mohamad Fathan Masloman; Gilang Ramadhan S. Luawo; Jim Mardin Wanimbo; Sintya Paula Junaedy; Franky Gerald Cliford Manoppo (International Journal Labs, 2026)
Accurate temperature monitoring is essential in laboratory and industrial operations involving furnaces to ensure process consistency, prevent overheating, and support safety compliance. Traditional monitoring methods, such as analog gauges or standalone digital thermometers, provide only instantaneous readings and fail to store historical data or visualize trends, limiting experimental reproducibility and quality control. This study aims to design, implement, and evaluate a low-cost, real-time data logging and historical graphing system for furnace temperature monitoring at the Electrical Engineering Laboratory of Politeknik Negeri Manado. The system integrates Type K thermocouples, MAX6675 thermocouple-to-digital modules, Arduino Uno microcontrollers, and a Python-based visualization application. The research employed an applied R&D approach, including stages of literature review, requirements analysis, system design, implementation, testing, and evaluation. Controlled experiments were conducted at five temperature set points, and a four-hour continuous logging test was performed to assess accuracy, logging continuity, and graphical performance. Results indicate that the system achieved a mean absolute error of 1.1°C, maintained uninterrupted data logging over 14,400 samples, and rendered real-time graphs with stable CPU usage. The findings confirm that the integrated system meets design specifications, providing a reliable and educationally valuable tool for laboratory use. This study concludes that low-cost, modular data logging solutions can effectively enhance instrumentation education and support precise thermal monitoring, with potential for further improvements in multi-channel and cloud-based monitoring systems.